2009
DOI: 10.1089/scd.2009.0054
|View full text |Cite
|
Sign up to set email alerts
|

Selective Culture of Mesodermal Progenitor Cells

Abstract: We have recently identified mesodermal progenitor cells (MPCs) isolated from adult human bone marrow. These cells show unusual phenotypes, having putative embryonic markers and aldehyde dehydrogenase (ALDH) activity. Interestingly, these resting cells, which have been selected by culturing them in the presence of adult human serum, can easily be induced to differentiate into mature mesenchymal stromal cells (MSCs) after substituting the adult human serum for fetal bovine serum (FBS) or human cord serum. MPC-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(58 citation statements)
references
References 11 publications
2
56
0
Order By: Relevance
“…The selective culture conditions described here have allowed the isolation of a novel adherent and almost monomorphic cell population as 1.0% of the hBM-MNCs (0.5 -2.0 x 10 6 hBM-MNCs from 5 -10 ml of fresh BM samples) 5,6 . We identified these large (40 -60 µm in diameter), rounded, quiescent, Ki-67-negative cells as MPCs 5 .…”
Section: Representative Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The selective culture conditions described here have allowed the isolation of a novel adherent and almost monomorphic cell population as 1.0% of the hBM-MNCs (0.5 -2.0 x 10 6 hBM-MNCs from 5 -10 ml of fresh BM samples) 5,6 . We identified these large (40 -60 µm in diameter), rounded, quiescent, Ki-67-negative cells as MPCs 5 .…”
Section: Representative Resultsmentioning
confidence: 99%
“…In our hands replacement of FBS with PhABS in primary cultures from hBM-MNCs, combined with high density seeding on hydrophobic plastics, led to the isolation of a novel highly adherent cell population with distinct biological features named MPCs 5,6 . We observed that the addition of small percentages of PhABS to FBS primary cultures also allowed MPC isolation, suggesting the presence of MPC inducing agents in the human serum 6 . At the moment, the MPC isolation/ characterization protocol is a unique method available to obtain almost pure MPCs.…”
Section: Representative Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other investigators recommend the cultivation in autologous human serum allowing a higher purification of the CB-MSC population [68].…”
Section: Embryonic Sc (Esc) Trans-differentiationmentioning
confidence: 99%